Governing khat: Drugs and democracy in Somaliland - Peter Hansen (Danish Institute for International Studies (DIIS), 2009)
This new DIIS Working Paper examines the role of the mild stimulant khat in the economic and political transformation of the independent, yet internationally unrecognized Republic of Somaliland. Rather than seeing khat as a hindrance for nation-state formation and as a developmental problem, the paper argues that khat has been important to the economic viability of Somaliland and to the formation of political practices and identities. Khat was linked to the collapse of the Somali state, but has also been instrumental in securing peace in Somaliland in the early 90s. In this sense, khat should be seen not only as a drug contributing to violence, state failure and inadequate development, but also as underpinning economic processes, political identities and societal structures that have been crucial to the formation and political success of Somaliland. In examining the role of khat in Somaliland, the paper adds to our understanding of the links between emerging political and economic orders in post-conflict societies.
Keywords: 330; Drogenkonsum; Entwicklung; Sozialer Wandel; Demokratisierung; Somalia